Hypothenar island flap: A safe and excellent choice for little finger defects - Mehmet Tapan; Murat Iğde; Ali Rıza Yıldırım; Yağmur Yaprak Balı; Sedat Yılancı; Ramazan Erkin Ünlü (Indian Journal of Plastic Surgery, 2015)
Soft-tissue defects of the little finger are challenging especially when bone, tendon or vascular pedicle is exposed because of trauma. The hypothenar island flap is easy to harvest and has a good colour and texture match to the little finger pulp. We present nine clinical cases of soft tissue defects of the little finger covered using the reversed hypothenar fasciocutaneous island flap. This article intends to highlight the ease of elevation and good clinical results of the hypothenar flap which is rarely used.